Mental Imagery, Psychology, and Rhetoric: An Examination of Recurring Problems - Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 1995)
The parallel debates on mental imagery in contemporary psychology and classical rhetoric have led to its marginal status in composition studies.